2020
DOI: 10.1111/1462-2920.15262
|View full text |Cite
|
Sign up to set email alerts
|

Rare taxa maintain the stability of crop mycobiomes and ecosystem functions

Abstract: Plants harbour highly diverse mycobiomes which sustain essential functions for host health and productivity. However, ecological processes that govern the plant-mycobiome assembly, interactions and their impact on ecosystem functions remain poorly known. Here we characterized the ecological role and community assembly of both abundant and rare fungal taxa along the soil-plant continuums (rhizosphere, phyllosphere and endosphere) in the maize-wheat/barley rotation system under different fertilization practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
128
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 165 publications
(156 citation statements)
references
References 85 publications
16
128
1
Order By: Relevance
“…These ndings are consistent with previous studies showing that plant compartment is a determining factor shaping the assembly of plant-associated microbiomes [26][27][28][29]42], and that plant seasonal status has signi cant effects on microbiomes in grasses phyllosphere and Arabidopsis rhizosphere [32,71]. Further, metagenomic analysis in our study revealed that the functional diversity and enriched functional traits in the maize phylloplane varied across three stages.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These ndings are consistent with previous studies showing that plant compartment is a determining factor shaping the assembly of plant-associated microbiomes [26][27][28][29]42], and that plant seasonal status has signi cant effects on microbiomes in grasses phyllosphere and Arabidopsis rhizosphere [32,71]. Further, metagenomic analysis in our study revealed that the functional diversity and enriched functional traits in the maize phylloplane varied across three stages.…”
Section: Discussionsupporting
confidence: 93%
“…To assess the relative importance of determinism and stochasticity in microbiome assembly, we calculated the beta Nearest Taxon Index (βNTI) using null model (999 randomizations) [59], and de ned |βNTI| ≥ 2 as dominant deterministic processes and |βNTI| < 2 as dominant stochastic processes [60,61] Microbial interkingdom network analysis at bacterial and fungal genus level was performed using the CoNet [62] in Cytoscape (v3.5) [63] based on Spearman correlation scores (Spearman's r > 0.7 or r < −0.7; P < 0.01). Both bacterial and fungal genera present in at least 10 samples were retained for the network analysis [42]. The networks were visualized in Gephi [64].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Total DNA was extracted from the aforementioned samples using the FastDNA SPIN Kit for Soil (MP Biomedicals, Solon, USA) following manufacturer's instructions. The V5-V6 region of bacterial 16S rRNA gene (799F-1115R) [14,51], and the ITS2 region (fITS7-ITS4) of fungal ITS [16,52,53] were ampli ed ( Table S1). The primers sequence and PCR ampli cations were shown in Table S1.…”
Section: Dna Extraction and Ampli Cation Sequencingmentioning
confidence: 99%